A review on independent and integrated/coupled two-phase loop thermosyphons. (15th December 2020) - Cao, Jingyu; Zheng, Zhanying; Asim, Muhammad; Hu, Mingke; Wang, Qiliang; Su, Yuehong; Pei, Gang; Leung, Michael K.H.
Highlights: First comprehensive review on two-phase loop thermosyphon technology. Characteristics, mechanism, and research progress of two-phase loop thermosyphon. Independent two-phase loop thermosyphon for effective heat transfer. Novel integration and coupling with vapour compression cycle. Challenges and prospects of two-phase loop thermosyphon technology. Abstract: Two-phase loop thermosyphon is a natural phase-change heat transfer cycle widely used for thermodynamic applications. In additon to low manufacturing and maintenance costs, the primary advantages of such device include high heat transfer capability, reliability, and sustainability. Significant progress has been made in the two-phase loop thermosyphon and its integrated/coupled systems for energy conservation and environment protection. This paper represents a comprehensive review that discusses the physical mechanisms, characteristics and research progress of the two-phase loop thermosyphon based on recent experimental and simulative studies. The review extends to worldwide applications of independent two-phase loop thermosyphon in the renewable and sustainable energy fields and its utilisation for performance enhancement of vapour compression cycles by system integration and coupling. Challenges and recommendations for future research and application of two-phase loop thermosyphon are identified. This review will help researchers and engineers better understand the mechanisms, features and potential of the two-phase loop thermosyphon technology and promote its development.